Family Transformation Toward Sakinah: A Review of Tarekat Naqsabandiyah Khalidiyah Role in Darul Ulum Islamic Boarding School Turi Panekan Magetan - Choirul Daroji (QURU’: Journal of Family Law and Culture, 2024)
Marriage is a very sacred ceremony, which aims to achieve happiness and in fact this marriage ceremony is inseparable from the rules set out in religious law. The main goal is to form a family filled with love and affection. However, in this day and age, the concept of family has lost its spiritual dimension as a means of worship to the Creator. Marriage is often considered a mere formality process, a social agreement between two individuals of different genders. As a result, the sacred meaning of marriage, where God is the witness to the covenant, is dimmed due to the lack of spirituality that pervades society. Family well-being is often measured in material terms, while spirituality plays a more important role. Therefore, the author is interested in examining families that have more value in the spiritual aspect, especially families related to tarekat. The purpose of this study is to uncover the impact of tarekat teachings on family well-being. In this article, the theory of spiritual intelligence is used as a foundation. The research method used is descriptive-analytical field research, using phenomenological and psychological approaches. Data were collected through interviews with primary sources consisting of murshids and students of the Naqsabandiyah Khalidiyah tarekat, as well as using secondary sources in the form of references from relevant books and journals. The results showed that marriage involves divine and human commitments, and is a social covenant. The implementation and role of the family in the Naqsabandiyah Khalidiyah tarekat take place as families in general. Therefore, tarekat can be considered as an alternative solution in forming a spiritually prosperous family